A THEORETICAL APPROACH TO THE INTERPRETATION OF LEXICAL UNITS OF TRANSLATOR, A GUIDE-TRANSLATOR AND A TOUR GUIDE - Alimova Kamola Tursunovna (Western European Studies, 2024)
This article discusses and analyzes the theoretical approach to the interpretation of lexical units’ translator, a guide-translator and a tour guide, as well as examples with possible equivalents
Keywords: translation; theoretical; meaning; equivalent